2013
DOI: 10.1073/pnas.1316609111
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical calculations suggest that lytic polysaccharide monooxygenases use a copper-oxyl, oxygen-rebound mechanism

Abstract: Lytic polysaccharide monooxygenases (LPMOs) exhibit a mononuclear copper-containing active site and use dioxygen and a reducing agent to oxidatively cleave glycosidic linkages in polysaccharides. LPMOs represent a unique paradigm in carbohydrate turnover and exhibit synergy with hydrolytic enzymes in biomass depolymerization. To date, several features of copper binding to LPMOs have been elucidated, but the identity of the reactive oxygen species and the key steps in the oxidative mechanism have not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
279
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 211 publications
(319 citation statements)
references
References 46 publications
27
279
4
Order By: Relevance
“…This order of events is in accordance with the notion that molecular oxygen tends to bind copper proteins when the metal ion is in the reduced monovalent state (59). Subsequent to dioxygen binding, the catalytic cycle is initiated, which results in substrate hydroxylation, followed by elimination to cleave the glycosidic linkage (10,11). This general mechanism will incorporate a single oxygen atom from molecular oxygen into the products.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This order of events is in accordance with the notion that molecular oxygen tends to bind copper proteins when the metal ion is in the reduced monovalent state (59). Subsequent to dioxygen binding, the catalytic cycle is initiated, which results in substrate hydroxylation, followed by elimination to cleave the glycosidic linkage (10,11). This general mechanism will incorporate a single oxygen atom from molecular oxygen into the products.…”
Section: Discussionsupporting
confidence: 83%
“…tively, in an AA9 LPMO with a similar ASM approach (11). Interestingly, the charge distribution of the coordinating histidine residues does not show a significant change, despite the substantial change in the copper ion oxidation state.…”
Section: Lpmo Copper Oxidation State Determination By Analogy To Smalmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar difference has been observed when comparing a strictly C1-oxidizing LPMO10 with an LPMO10 that can oxidize both C1 and C4 (17). It has been shown that end-on binding of dioxygen is energetically favorable (12,49); however, although Kim et al (49) model O 2 binding at the exposed axial position, Kjaergaard et al (12) propose a model where the equatorial OH ligand is replaced by O 2 . This discrepancy is probably a result of different initial structural models and basis sets used in the density functional theory (DFT) calculations.…”
Section: Discussionmentioning
confidence: 65%
“…Although binding of multiple bivalent metal ions has been observed in the crystal structures for several LPMOs (5,17), available experimental and theoretical data consistently indicate that the active site copper centers are mononuclear (11,12,17,49). The additional metal ions observed in the zinc structure of NcLPMO9C are coordinated by amino acids belonging to a sequence insertion unique for strictly C4-oxidizing LPMO9s, but Fig.…”
Section: Discussionmentioning
confidence: 98%